Enhancing crop growth and management of bacterial wilt disease in ginger by potential Bacillus strains through induced systemic resistance - Moilothum Kandiyil, Theertha Anilkumar; Saraswathy Amma, Dileep Kumar Bhaskaran Nair; Nair, Kesavachandran Chandrasekharan (Biocontrol science and technology, 2024)
Bacterial wilt disease, caused by Ralstonia solanacearum poses a severe threat to ginger plants. The present study aimed to determine the effect of Bacillus strains to combat R. solanacearum-induced bacterial wilt in ginger by inducing defense enzymes viz., peroxidase(POX), Polyphenol oxidase (PPO), Phenylalanine ammonia-lyase (PAL) and total phenol content, while also promoting growth and yield. The Bacillus strains were isolated from soil samples collected from the Western Ghats, one of India's biological diversity hot spots through random sampling. Two strains exhibiting better antagonistic activity were identified as Bacillus spp through 16S rRNA sequencing. Pot studies were conducted to evaluate the biocontrol efficacy and plant growth promoting ability of these bacterial strains against R. solanacearum. Results showed that ginger plants treated with NIIST NB120 significantly increased shoot length 70.80 cm, leaf length 30.03 cm, leaf breadth 3.42 cm, number of leaves 22, and yield 355.81% compared to plants treated with R. solanacearum, which had lower values. Furthermore, plants treated with NIIST NB120 had the lowest bacterial wilt incidence at 25%, in contrast to 66% in plants treated with pathogen. Application of Bacillus strains also enhanced the activities of defense-related enzymes, including, PAL 0.030 units/ g tissue, PPO 0.0016 units/ g tissue, POD 68.28 units/ g tissue, and total phenolic content 219.5 units/ g tissue, with the lowest enzyme activity observed in pathogen treated plants. These findings suggest that the Bacillus strains NIIST B16 B. siamensis and NIIST NB120 B. amyloliquefaciens could be effective biocontrol agents of ginger bacterial wilt disease.